Re-considering Processual and Post-Processual Archaeology: Can a Historical Approach Help Nuance the Usage of aDNA and Archaeogenetics - Andersson, Adam (Archaeologia Lituana, 2023)
This article addresses the question of the use of modern archaeogenetics, taking into account the history of the discipline of archaeology itself, and comparing the criticisms that processual archaeology received with the criticisms that are currently directed to the use of archaeogenetics and “new” scientific methods. This paper illustrates that there are several parallels between processual archaeology in the 1980s and the criticisms received by contemporary users of archaeogenetics. This can be seen by examining the criticism that both have received and are currently receiving. This article aims to stimulate discussion about how the discipline best applies these scientific methods which are being increasingly used. The paper likewise aims to add to the discourse on how the discipline of archaeology best moves beyond the current concept of mobility and how a historical approach can be useful. At the same time, the work tries to emphasize the importance of learning from the history of one’s discipline and why it is worth taking history as a starting point.
Keywords: archaeogenetics; aDNA; critical historiography; mobility; processual archaeology; post-processual archaeology; history of archaeology